A measure of fast ion beta at marginal stability in the reversed field pinch. (27th June 2019) - Capecchi, W.; Anderson, J.K.; Bonofiglo, P.J.; Kim, J.; Magee, R.M.; McCollam, K.J.; McConnell, R.; Parke, E.; Sarff, J.S.
Abstract: Energetic ions are well confined in the core of the reversed field pinch and a substantial population develops rapidly during tangential neutral beam injection. A saturated fast ion density is observed within several milliseconds and coincides with the onset of energetic particle mode activity. First measurements of the fusion product profile determine the fast ion density and pressure profiles, the latter of which when combined with neutral particle analysis of the energy distribution. These are key measurements in explaining the limiting behavior of the fast ion profile in response to a combination of effects. Tearing mode activity affects the fast ion profile, and the fast ions noticeably influence the core-most tearing mode. The nonlinear situation settles into a marginally stable state where the EPM transports fast ions down a steep gradient to a region where their confinement is limited by stochastic orbit and charge exchange losses. In the state at marginal stability (achieved in one set of experimental conditions with full 1 MW neutral beam power), a critical fast ion beta gradient is measured that limits the core, or nearly four times the core thermal, but less than a strictly classical calculation predicts.